Images of choroid by optical coherence tomography in healthy subjects and chorioretinal diseases - Cruzado-Sánchez, Deivy Robert (2013)
Objectives: Describe the images of the choroid by optical coherence tomography (OCT) spectral domain in healthy subjects and chorioretinal diseases. Materials and methods: Case series study. We evaluated 67 cases involving healthy ocular subjects and patients with chorioretinal diseases. The scans included a sweep of the retina and choroid at level of the macula conventionally, and other using enhanced depth imaging (EDI). The choroid thickness was measured from the outer edge of the retinal pigment epithelium to the internal scleral rim. Results: Of the 67 cases, 12 (17.4%) were healthy ocular subjects, 10 (14.5%) with central serous chorioretinopathy (CSC), 23 (33.4%) agerelated macular degeneration (AMD), 9 (13.0%) with myopia, 13 (18.8%) with polypoidal choroidal vasculopathy. There are differences in the quality of images with conventional OCT and those with EDI, allowing only to describe the choriocapillaris in some cases while the EDI protocol can appreciate the total thickness of the choroid. The choroid is thicker in polypoidal choroidal vasculopathy (353.92 ± 68.66 microns) and CSC (408.81 ± 95.56 microns) than in healthy subjects (251.97 ± 66.37 mm) (p<0.05) and is decreased in the dry AMD (124.69 ± 34.02 microns) (p<0.05), as well as in the myopia (118.47 ± 34.02 microns) (p<0.05). Conclusions: OCT images of the choroid by PIM is a reproducible technique for describing and measuring its thickness, being decreased in AMD and myopia, and was increased in the polypoidal vasculopathy and CSC.